Renal Apparent Diffusion Coefficient Values in Patients with Obstructive Uropathy and High Values of Creatinine - Sonmezgoz, F.; Kalayci, T. O.; Karakeci, A.; Karasu, S. (Ubiquity Press Ltd, 2015)
Purpose: Diffusion weighted magnetic resonance imaging (DW-MRI) of the kidneys provides noninvasive information on renal function in healthy volunteers, and it is feasible in severely ill patients. It may provide information on the degree of kidney dysfunction. The purpose of this study is to evaluate apparent diffusion coefficient (ADC) values using DW-MRI in patients with obstructive uropathy and elevated serum creatinine levels. Methods: Fifty patients with high serum creatinine levels and diagnoses of chronic urinary obstruction detected by ultrasonography were included in this study. DW-MRIs were obtained from 50 patients with hydronephrotic kidneys and 26 healthy volunteers using a 1.5T whole-body MR scanner. Results: ADC measurements of renal parenchyma in hydronephrotic kidneys were significantly lower compared to normal kidneys (p < 001). Conclusion: The measurement of ADC values has potential value in the evaluation of the functional status of hydronephrotic kidneys.
Keywords: Kidney; stenosis or obstruction - Kidney; MR